PENGARUH PENYARADAN TERHADAP KERUSAKAN TEGAKAN TINGGAL PADA BERBAGAI TINGKAT KELERENGAN - Dulsalam Dulsalam; Sukanda Sukanda (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
An investigation or the effect of skidding to residual stand damage on several slope degrees has been done at PT Sumpol Timber in South Kalimantan in 1987. The purpose of this investigation is to seek information on the residual stand damage caused by skidding on several slope degrees. The investigation took place in three different slope degrees: i.e.: 0 - 20 %, 20 - 40 %, and > 40%. Sample plots were selected with completely randomized design.Results of this investigation are concluded as follows :Skidding has caused part of the residual stand to damage.The residual stand damage caused by skidding ranges from 10 Trees/ha to 70 trees/ha (from 6 % to 29 %) with an average of 30 trees/ha (15%) with standard error of 3,60 trees/ha. The residual stand damage caused by skidding on : a. 0 - 20 % slope ranges from 10 trees/ha to 50 trees/ha (6 – 18%) with an average of 23,3 trees/ha (11 %). b. 20 - 40 % slope ranges from 10 trees/ha to 70 trees/ha with an average of 30 trees/ha (15 %). c.Greater than 40 % slope ranges from 20 trees/ha to 70 trees/ha (from 10 % to 29 %) with an average of 38 trees/ha (19 %).The result of Least Significant Difference (LSD) test on the data revealed that the residual stand damage between 0 - 20% and > 40% slope differs significantly at 95% level. The higher the slope degree the greater the residual stand damage took place.It is therefore sugessted that skidding on 40 % slope degree or more be done with great care in order to decrease the residual stand damage